The use of vancomycin-soaked wrapping of hamstring grafts to reduce the risk of infection after anterior cruciate ligament reconstruction: An early experience in a district general hospital - Keith Hay-Man Wan; Stephen Pui-Kit Tang; Richard Hin-Lun Lee; Kevin KH Wong; Kam-Kwong Wong (Elsevier, 2020)
Abstracts: Introduction: The purpose of the study was to investigate whether pre-soaked hamstring graft with a solution of vancomycin followed by the 'vancomycin wrap' provides an effective way to reduce the risk of post-operative infection. We hypothesized that with the addition of the 'vancomycin wrap' there would be a significant reduction in the risk of post-operative infection. Methods: A retrospective review of data collected on 305 consecutive patients who underwent anterior cruciate ligament reconstruction (ACLR) with hamstring autograft from April 2012 to March 2019. In the initial 4-year period, 185 patients (group 1) underwent ACLR with pre-operative intravenous antibiotic. In the subsequent 3-year period, 120 patients underwent ACLR with vancomycin pre-soaked graft together with pre-operative intravenous antibiotic before tourniquet inflation. After graft harvest, the grafts were soaked into a 5 mg/ml vancomycin solution for 1 min. The graft was then fastened within the graft sizing tube and wrapped by a sterile gauze saturated with the vancomycin solution beforehand. Results: A total of 3 culture-positive joint infection were documented (1.6%) in group I, requiring arthroscopic debridement. In group 2 no infection (0%) was recorded. Conclusions: We proposed a safe, simple and easy-to-do method to reduce the risk of such complication.Prophylactic vancomycin soaking of hamstring autograft is effective to reduce the infection rate in this series compared with pre-operative antibiotic alone.